Implementation of the Discrete Wavelet Transform (DWT) Steganography Method for Embedding Secret Messages in Digital Image Media - Jahanra Girsang; Abed Tanjung (BIOS: Jurnal Informatika dan Sains, 2025)
Steganography is a technique for hiding confidential information within a digital medium so that the existence of the information is not easily detected by unauthorized parties. Digital images are commonly used in steganography because they contain high data redundancy and are widely used in modern communication. One effective approach in image steganography is the transform domain approach, particularly the Discrete Wavelet Transform (DWT). DWT transforms image representation from the spatial domain into a multi-resolution frequency domain consisting of several sub-bands. Secret message embedding is performed in certain frequency sub-bands that are not highly sensitive to human visual perception, thereby preserving the quality of the stego image. This study aims to implement a DWT-based steganography method and evaluate its performance based on stego image quality and message extraction success. The evaluation is conducted using Peak Signal-to-Noise Ratio (PSNR) and Mean Square Error (MSE) metrics. The test results show that the DWT method is capable of producing stego images with very good visual quality, with an average PSNR value above 40 dB, and a 100% message extraction success rate. This demonstrates that the DWT-based steganography method is effective in maintaining digital information security.